Halal, Health, or Hype? Generational Shifts in Ready-to-Drink Coffee Preferences in Indonesia’s Semi-Urban Markets: Halal, Kesehatan, atau Tren? Pergeseran Preferensi Kopi Siap Minum Antar Generasi di Pasar Semi-Urban Indonesia - Akbar Maulana Firmansyah; Fariza Rachman (Journal of Business Management, 2025)
The rapid growth of Indonesia’s ready-to-drink (RTD) coffee market, fueled by urbanization and shifting consumer lifestyles, underscores the need to understand how cultural, religious, and globalized factors shape purchasing decisions, particularly among younger generations in semi-urban regions. This study investigates the relative influence of Halal certification, health labels, and brand origin (international versus local) on Gen Y and Gen Z consumers in Jember, East Java, a Muslim-majority semi-urban market. Using a quantitative cross-sectional design with a sizeable number of respondents, the research combined validated Likert-scale surveys and statistical analyses, including logistic regression and factor analysis, to test hypotheses derived from consumer behavior theories. Results revealed Halal certification as the strongest predictor for both generations, although Gen Z reinterpreted Halal as a quality marker rather than a religious obligation. Health labels demonstrated a negligible impact that was overshadowed by taste and price preferences. Brand origin preferences diverged sharply, with Gen Y favoring international brands while Gen Z exhibited a hybrid glocal identity that balances local cultural resonance with global trends. These findings highlight generational shifts in religiosity, the legacy of globalization, and the challenges of health positioning in indulgence-driven markets. The study offers actionable insights for marketers to tailor RTD coffee strategies by prioritizing Halal compliance for trust, leveraging Gen Z’s digital engagement for glocal branding, and innovating sensory-driven health claims. Theoretically, it advances consumer behavior literature in emerging markets by contextualizing the interplay of cultural authenticity, generational identity, and ethical consumption.